Hard Content, Fab Front-End: Archiving Websites of Dutch Public Broadcasters. Issue 1 (1st August 2014) - Baltussen, Lotte Belice; Blom, Jaap; Medjkoune, Leïla; Pop, Radu; Van Gorp, Jasmijn; Huurdeman, Hugo; Haaijer, Leidi
Abstract: Although there are a great variety of web archiving projects around the world, there are not many that focus explicitly on websites of broadcasters. The reason is that funds are often lacking to do this, and that broadcaster websites are difficult to archive, due to their dynamic and audiovisual content. The Netherlands Institute for Sound and Vision, with its collection of over 800, 000 hours of audiovisual content has been involved in a smallscale research project related to web archiving since 2008. When Sound and Vision was approached by Dutch public broadcaster NTR to archive four of its websites, it was decided to start a collaborative pilot project that focused both on learning more about archiving broadcaster websites and developing a clean and modern public access interface. The main lesson learned from this pilot is that to archive highly dynamic and AV-heavy broadcaster websites it is vital to use supplementary capture tools and manual archiving of this 'difficult' content. Furthermore, since the focus of web archiving projects is usually not on a good-looking front-end, the wheel had to be partly re-invented by involving various stakeholders and determining the most important requirements. The first version of the web archive was evaluated by various prospective target users. This evaluation revealed that the participants indeed appreciated the look and speed of the web archive, and that users needed to be made more aware of the web archive's purpose and limitations. The work will be continued and scaled up, by archiving more broadcaster websites, continuing the research on how best to capture and make accessible dynamic and AV content, and by creating standard practices for making the web archive publicly available.